Keterlibatan Mahasiswa Calon Guru IPA dalam Pembelajaran Filsafat Sains Berbasis Game Multiplatform: Analisis Deskriptif dan Item-Level - Rifda Nur Hikmahwati Arif; Salma Samputri (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2026)
Philosophy of Science courses in pre-service science teacher education face persistent engagement challenges due to the abstract nature of ontological, epistemological, and axiological content. This study describes the level and item-level profile of Behavioral, Emotional, and Cognitive Engagement among pre-service science teachers in a multiplatform game-based learning (GBL) Philosophy of Science course, and documents game preferences and learning expectations. A survey design was employed with 78 pre-service science teachers (Angkatan 2024) from three parallel class sections at Universitas Negeri Makassar. A validated 24-item Student Engagement Instrument grounded in Fredricks et al. (2004) with six reverse-scored items assessed three engagement dimensions (α=.900). Overall engagement was High (M=4.330, SD=0.447), with Behavioral (M=4.442) and Emotional (M=4.449) dimensions reaching Very High. Item-level analysis identified active participation, rule-following, and academic pride as highest-scoring items, while C8 — 'material remains too abstract even in games' (M=3.513) — served as the primary diagnostic indicator of a persistent abstraction barrier. No significant between-class differences were found (all p>.05). All engagement dimensions were strongly intercorrelated (rs=.613–.822). Offline games were most preferred (42.3%), with Quizizz dominating digital preferences (78.2%).